EFFECT OF DIETARY FACTORS AND NUTRITIONAL STATUS ON SERUM CALCIUM AND PHOSPHORUS LEVELS IN CKD PATIENTS ON TREATMENT IN A TERTIARY CARE SETTING IN NORTH INDIA - Bansal, Babita; Takkar, Jaspreet; Agrawal, Deepak; Gahlot, Sushila (Universal Journal of Pharmaceutical Research, 2020)
Objective: The control of phosphorus and calcium metabolism is one of the objectives in treatment protocol for CKD patients. The levels of these minerals in serum are affected by dietary patterns and nutritional status of the patients. India being a large country, diet patterns vary from one state to another. Thus, we suspect a close association between dietary intake and alterations in homeostasis of calcium and phosphorus in CKD patients. Therefore, we conduct this study to describe the effect of dietary factors and nutritional status on serum calcium and phosphorus levels in CKD patients on treatment in a tertiary care setting in North India. Methods: In the present study 330 CKD patients coming to dialysis unit, were recorded with detailed Medical history as well as baseline demographic data. Also, biochemical analysis of serum albumin corrected, calcium, phosphorus, and serum albumin of all cases were done using fully automated equipment. All statistical analyses were performed using SPSS statistical software. Results: Majority (58.2 %) of the study patients were vegetarians with a mean value of BMI (Mean±SD=23.75±4.70 kg/m2). A negative but significant correlation was found between corrected calcium and phosphorus with 0.05 level of confidence interval (r=-0.149, p= 0.007). Conclusion: It was found that the well-nourished patients were more likely to be hyperphosphatemic as compared to poorly nourished patients, but statistically the values were found to be nonsignificant (Statistically p-value was not less than 0.05). Peer Review History: Received 2 October 2019; Revised 7 November; Accepted 28 December; Available online 15 January 2020 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dina Abd Elfattah Eldakhs , Pharos university (PUA), Egypt, dina_eldakhs@yahoo.com Dr. Mohammad Tauseef , Department of Pharmaceutical Sciences, College of Pharmacy, Chicago State University, mtauseef@csu.edu